Unveiling Ethnoparenting in Early Childhood Education: Parenting Culture and Religious Values in Madura, Indonesia - Fitroh, Siti Fadjryana; Latif, Muhammad Abdul; Yuandana, Tarich; Trisetiawati, Jelita; Dwi Aprilia, Winda; Pinias, Chikuvadze (Jurnal Pendidikan Agama Islam, 2026)
Purpose – Despite growing concerns about child protection in Bangkalan, Madura, limited research has examined how culturally grounded parenting practices shape collaboration between families and Islamic early childhood education institutions. This study aims to explore the practice of ethnoparenting in Islamic Early Childhood Education institutions in Madura, particularly focusing on child-rearing practices that emphasize religious values, moral discipline, and home–school collaboration. Design/methods/approach – This study employed a qualitative multiple-case study design involving seven parents selected through purposive sampling from three Islamic Early Childhood Education (ECE) institutions in Madura: TK ABA Socah, TK Muslimat NU Darunnajah Kamal, and TK YKK 1 Bangkalan. Data were generated through in-depth interviews, observations, and document analysis, and were examined using thematic analysis to identify patterns of ethnoparenting practices and their perceived implications for child development within Islamic educational contexts. Findings – The findings reveal that ethnoparenting is operationalized through the integration of local Madurese traditions and Islamic teachings in both parental practices and school routines. Religious and cultural values are systematically internalized through moral habituation, dialogical discipline, and sustained home–school collaboration. This approach contributes to the development of children’s moral awareness, social responsibility, and respectful behavior, particularly in relation to elders and community norms. Research implications/limitations – The study offers implications for culturally grounded and faith-based child-rearing policies in Islamic ECE contexts. However, as the research was conducted in a single region and institutional type, the findings may not be fully transferable to other contexts. Originality/value – This study contributes to the limited scholarship on ethnoparenting in Madura by demonstrating how religious and cultural values are operationalized in everyday pedagogical practices within Islamic ECE institutions.